Perovskite quantum dot with fluorine-containing passivation layer and construction method of fluorine-containing passivation layer

By forming a fluorine-containing passivation layer on the surface of perovskite nanocrystals, the problem of structural damage and luminous performance of perovskite nanocrystals in high temperature and light environments is solved, and higher stability and luminous performance are achieved.

CN119552658AActive Publication Date: 2025-03-04WENZHOU XINXIN TAIJING TECH CO LTD

Patent Information

Application Number
CN202410126814.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2025-03-04
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

Perovskite nanocrystals are prone to structural damage in high temperature, high humidity and strong light irradiation environments, resulting in a degradation of luminescence performance. The existing coated structure cannot effectively passivate its surface, resulting in a decrease in fluorescence intensity.

Method used

Using perovskite quantum dots with fluorine-containing passivation layer, the defects on the surface of the perovskite nanocrystals are blocked and passivated by growing perovskite nanocrystals in the pores of the micro/mesoporous template and forming fluorine-containing passivation layers such as BaF2 on their surface.

Benefits of technology

Effectively reduce the surface defect density of perovskite nanocrystals and improve its stability and luminous performance under high temperature and light environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552658A_ABST
    Figure CN119552658A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite quantum dot with a fluorine-containing passivation layer, the perovskite quantum dot comprises a micro / mesoporous template with incompletely closed pores, perovskite nanocrystals and the fluorine-containing passivation layer grow in pores of the micro / mesoporous template, and the fluorine-containing passivation layer is used for passivating surface defects of the perovskite nanocrystals; and the fluorine-containing passivation layer comprises BaF2 (BaF2). According to the method, the surface of the perovskite nanocrystal can be passivated without collapsing the micro / mesoporous template, so that the stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite quantum dots, and in particular relates to a perovskite quantum dot with a fluorine-containing passivation layer and a method for constructing the fluorine-containing passivation layer. Background Art

[0002] Lead halide compounds with perovskite structure are an emerging semiconductor material, especially the all-inorganic perovskite CsPbX3 (X = Br, Cl, I), which has high fluorescence quantum yield, narrow half-width and adjustable emission wavelength, and has great research and application value in lighting and display devices. However, since lead halide perovskite is an ionic compound with soft lattice characteristics, it is easy to cause structural damage in environments such as high temperature, high humidity, and strong light irradiation, resulting in a decrease in its luminescence performance, which hinders the actual luminescence application of perovskite materials. For example: the lead hydroxide coating layer such as PbBrOH that is spontaneously generated by perovskite nanocrystals in water has good water and oxygen barrier ability, but when the temperature is higher than 70 degrees Celsius, due to the gradual decrease in the chemical stability of PbBrOH, the passivation of perovskite is destroyed, which significantly reduces the luminescence efficiency of nanocrystals.

[0003] Encapsulating perovskite nanocrystals in coating materials can effectively enhance their stability. For example, using mesoporous silica, molecular sieves and other materials that are prone to collapse at high temperatures as the coating structure of perovskite nanocrystals can well isolate perovskite from the external environment and ensure that perovskite nanocrystals emit light stably in water or high-humidity air. For example: Chinese patents with publication numbers CN110734758A and CN115772401A all require the micro / mesoporous template (mesoporous silica, molecular sieve) to collapse.

[0004] However, these coating structures usually cannot effectively passivate the surface of perovskite nanocrystals, resulting in a large number of surface defects in the perovskite nanocrystals. These defects will cause the fluorescence intensity of the perovskite nanocrystals to decrease in high temperature or light environments, so improvement is urgently needed. Summary of the invention

[0005] The object of the present invention is to provide a perovskite quantum dot having a fluorine-containing passivation layer and a method for constructing the fluorine-containing passivation layer. To achieve the above object, the technical solution adopted by the present invention is:

[0006] A perovskite quantum dot with a fluorine-containing passivation layer, comprising a micro / mesoporous template with incompletely closed pores, wherein perovskite nanocrystals and a fluorine-containing passivation layer are grown in the pores of the micro / mesoporous template, and the fluorine-containing passivation layer is used to passivate the surface defects of the perovskite nanocrystals;

[0007] The fluorine-containing passivation layer includes BaF2.

[0008] Furthermore, the fluorine-containing passivation layer is composed of BaF2 and other metal fluorides;

[0009] The other metal fluorides are metal fluorides other than BaF2.

[0010] Furthermore, when the micro / mesoporous template is MCM-41, the fluorine-containing passivation layer is composed of BaF2 and NaK2AI F6.

[0011] Further, the micro / mesoporous template is a microporous material and / or a mesoporous material;

[0012] The microporous material is a microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride;

[0013] The mesoporous material is mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.

[0014] Furthermore, the perovskite nanocrystal has a perovskite structure ABX3, wherein the molar ratio of A, B and X is 1:1:3, and A is Cs, B is Pb, Sn or Cu, and X is Cl, Br or I.

[0015] Furthermore, the perovskite nanocrystal has a perovskite structure ABX 1.5 X' 1.5 , wherein the molar ratio of A, B, X and X' is 1:1:1.5:1.5, and A is Cs, B is Pb, Sn or Cu, and X and X' are different and are independently Cl, Br or I.

[0016] Furthermore, the melting point of the fluorine-containing passivation layer (BaF2) is higher than that of perovskite nanocrystals. Therefore, BaF2 has higher lattice energy than perovskite nanocrystals, and its structure is stable and difficult to be destroyed. At this time, if BaF2 is attached to the inner wall of the micro / mesoporous template, it will play a role similar to a reinforcing rib on the micro / mesoporous template, thereby improving the structural strength of the micro / mesoporous template for subsequent production and processing.

[0017] Furthermore, a passivation interface is formed between the fluorine-containing passivation layer and the perovskite nanocrystal, thereby reducing the surface defect density of the perovskite nanocrystal.

[0018] Furthermore, the lattice of the fluorine-containing passivation layer is embedded with perovskite nanocrystals; or part of the perovskite nanocrystals are covered by the fluorine-containing passivation layer. If part of the perovskite nanocrystals are covered by the fluorine-containing passivation layer, there are more passivation interfaces between the fluorine-containing passivation layer and the perovskite nanocrystals, so that the passivation effect on the perovskite nanocrystals is better.

[0019] A method for constructing a fluorine-containing passivation layer of a perovskite quantum dot, comprising a micro / mesoporous template with incompletely closed pores, wherein perovskite nanocrystals containing barium are grown in the pores of the micro / mesoporous template, and a lead hydroxide coating layer is formed on the surface of the perovskite nanocrystals after being soaked in water;

[0020] It also includes F ions enriched in the pores of the micro / mesoporous template, and the lead hydroxide coating layer blocks the contact between the F ions and the perovskite nanocrystals containing the barium element; from another perspective: the lead hydroxide coating layer is located between the F ions and the perovskite nanocrystals containing the barium element to block the contact between the two.

[0021] Under the hydrothermal reaction, the lead hydroxide coating disappears and a BaF2 passivation layer is formed on the surface of the perovskite nanocrystals.

[0022] By adopting the above scheme: Hydrothermal reaction generally refers to the process in which a substance reacts under a high temperature and high pressure water environment. In the present application, the bonding of the highly negatively charged fluoride ions and the highly positively charged barium ions is facilitated by the hydrothermal conditions of high temperature and high pressure. The pressure of the hydrothermal reaction is between 1 and 100 MPa. The temperature of the hydrothermal reaction is >70°C, and the reaction time is at least 1 hour.

[0023] Furthermore, the lead-containing hydroxide coating layer and the fluorine-containing passivation layer appear one by one. The researchers found that the disappearance of the lead-containing hydroxide coating layer and the appearance of the fluorine-containing passivation layer occurred simultaneously. Considering the time dimension, the lead-containing hydroxide coating layer and the fluorine-containing passivation layer appeared in sequence.

[0024] Furthermore, when the fluorine-containing passivation layer is composed of BaF2 and other metal fluorides,

[0025] Other metal fluorides can be used as characterization and identification phases for constructing a fluorine-containing passivation layer of perovskite quantum dots through a hydrothermal reaction; for example, the other metal fluorides can be NaK2AI F6 as the characterization and identification phase.

[0026] When the micro / mesoporous template is MCM-41, the fluorine-containing passivation layer is composed of BaF2 and NaK2AI F6, and NaK2AI F6 is used as the characterization identification phase for constructing the fluorine-containing passivation layer of perovskite quantum dots through a hydrothermal reaction.

[0027] By adopting the above scheme: First, the researchers doped or modified the surface of the perovskite nanocrystals with metal barium so that the barium element existed on the surface of the perovskite nanocrystals. As the fluorine ions entered the pores of the micro / mesoporous template and reacted with the barium element to form BaF2, the BaF2 was located on the surface of the perovskite nanocrystals to passivate the perovskite nanocrystals.

[0028] If the micro / mesoporous template is doped or modified by other metals. The fluorine-containing passivation layer formed in the present application will be composed of BaF2 and other metal fluorides. For example: the fluorine-containing passivation layer is composed of BaF2 and NaK2AI F6, and the composition of the material can be identified by XRD. MCM-41 is a material with an ordered mesoporous structure, and its chemical composition is mainly silicon dioxide (SiO2), and does not contain metal elements such as potassium (K), aluminum (Al) and sodium (Na). However, other elements, such as metal cations or organic molecules, can be introduced during the synthesis of MCM-41 to change its physical and chemical properties. Other elements, such as potassium, aluminum and sodium, can be introduced into MCM-41 by methods such as co-doping or surface modification. These elements can be located in the pores or on the surface of MCM-41, thereby affecting its adsorption and other properties. At this time, it is easy to form other metal fluorides, such as NaK2AI F6, with fluoride ions under hydrothermal reaction conditions. NaK2AI F6 is used as the characterization identification phase for the fluorine-containing passivation layer of perovskite quantum dots constructed by hydrothermal reaction to obtain a Morse code-like structure.

[0029] At this time, the researchers also found that NaK2AI F6 is not the only characterization and identification phase. If different metal elements are introduced into the micro / mesoporous template or perovskite nanocrystal, different characterization and identification phases will be formed.

[0030] A method for preparing perovskite quantum dots comprises the following steps:

[0031] S1. Preparation of perovskite nanocrystals:

[0032] Mixing a perovskite nanocrystal precursor and a micro / mesoporous template to obtain a mixture; calcining the mixture at a temperature lower than the collapse temperature of the micro / mesoporous template, thereby generating perovskite nanocrystals in the pores of the micro / mesoporous template;

[0033] S2, hydrothermal post-treatment;

[0034] The perovskite nanocrystals obtained in step S1 are dispersed in a high-pressure reaction device filled with an inorganic fluoride solution, and the mixed solution is treated by a hydrothermal method to obtain perovskite quantum dots with a fluorine-containing passivation layer.

[0035] Further, the perovskite nanocrystal precursor includes a CsPbX3 perovskite nanocrystal precursor, and the CsPbX3 perovskite nanocrystal precursor is composed of a Cs source precursor, a Pb source precursor and a halogen source precursor;

[0036] Wherein: the Cs source precursor includes one or more of cesium halide and cesium carbonate;

[0037] The Pb source precursor includes one or more of lead halide and lead acetate;

[0038] The halogen source precursor includes one or more of cesium halide, lead halide, zinc halide, potassium halide, sodium halide, lithium halide, ammonia halide, calcium halide, strontium halide, and barium halide.

[0039] In addition, if the halogen source precursor includes both a bromine source and an iodine source, CsPbBr 3-y I y Perovskite structure. As a person skilled in the art, it is expected that the selection of different amounts of bromine and iodine sources to adjust the wavelength of quantum dot emission is possible. Therefore, the protection of perovskite nanocrystals in this application includes CsPbBr3, CsPb I3, CsPbBr y I 3-y Perovskite structure.

[0040] Furthermore, the inorganic fluoride solution includes an aqueous solution of NaF, KF, LiF, CsF and a combination thereof.

[0041] Further, as a preference, the hydrothermal reaction temperature in step S2 is between 150° C. and 250° C. Under the high temperature and high pressure conditions of the hydrothermal reaction, it is favorable for the bonding of the strongly negatively charged fluoride ions and the strongly positively charged metal ions to occur. For example, the pressure of the hydrothermal reaction is between 1 and 100 MPa.

[0042] Furthermore, the high-pressure reaction device in step S2 is a high-pressure reactor.

[0043] Furthermore, the calcination temperature of the perovskite nanocrystal precursor and the micro / mesoporous template is less than 600° C. to prevent the pore structure of the micro / mesoporous template from collapsing.

[0044] In the process of preparing the perovskite quantum dot material with a fluorine-containing passivation layer, the maximum calcination temperature used in the present invention is preferably to ensure that the pores of the micro / mesoporous material will not collapse. However, the collapse temperatures of different micro / mesoporous materials are different, and the collapse temperatures of the same material with different structures are also different, but it can be determined that in order to achieve better results, the calcination temperature must not be higher than the minimum collapse temperature of the material. For example, in the micro / mesoporous material exemplified above, the collapse temperature is as low as 300°C. In practice, generally speaking, 300 to 2000°C can ensure that most of the commonly used micro / mesoporous materials collapse. For example, mesoporous silica collapses at 600°C, mesoporous titanium dioxide begins to collapse at 800°C, and so on.

[0045] In addition, the "calcination under conditions lower than the collapse temperature of the micro / mesoporous template" defined in the present invention should also include the use scenarios of using fluxing agents. For example, the Chinese patent with patent application number ZL202211559323.5 also introduces a mesoporous material collapse agent in an attempt to reduce the collapse temperature of the micro / mesoporous material and achieve size control of the perovskite nanocrystals by avoiding agglomeration. It should be pointed out that even if a fluxing agent or collapse agent is added, the calcination temperature of the present application in the preparation of perovskite nanocrystals still needs to be "calcined under conditions lower than the collapse temperature of the micro / mesoporous template" to retain the existence of the pores.

[0046] The beneficial effects of the present invention are mainly reflected in:

[0047] 1. In the present invention, the micro / mesoporous template is not closed to retain nanopores. Since the ion diameter of F ions is about 0.26 nm, which is much smaller than the nanopores of the mesoporous template (the pore diameter is usually greater than 2 nm), F ions can be effectively enriched inside the micro / mesoporous template.

[0048] 2. Since F ions have strong electronegativity, they can bond with unpaired metal ions on the surface of perovskite (such as barium ions), thereby blocking and passivating the perovskite surface.

[0049] 3. Since perovskite quantum dots easily react with water, thereby reducing the luminescence performance, the field of perovskite display luminescence research usually has a technical prejudice that "water needs to be completely isolated during the preparation process of perovskite". However, the present application goes the other way and takes advantage of the fact that the PbBrOH and other lead hydroxide coatings that are spontaneously generated by perovskite nanocrystals in water have good water and oxygen barrier capabilities, but the chemical stability gradually deteriorates when the temperature is higher than 70 degrees. Before the PbBrOH and other lead hydroxide coatings fail, time is given for the F ions to effectively enrich in the micro / mesoporous template pores. After gradually raising the temperature to 70°C by the hydrothermal method, the PbBrOH and other lead hydroxide coatings are destroyed by the high temperature and high pressure environment provided by the high pressure reaction device. At this time, the F ions that have entered the micro / mesoporous template can immediately form bonds with the unpaired, positively charged metal ions (such as Ba ions) on the perovskite surface, thereby blocking and passivating the perovskite surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a spherical aberration transmission electron microscopy (AC-TEM) test image of the perovskite quantum dots obtained in Example 1;

[0051] Figure 2 1 is the XRD diagram of the perovskite quantum dots of Example 1 measured at various stages;

[0052] Figure 3 1 is the XRD diagram of the perovskite quantum dots of Example 2 measured at various stages. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0054] Embodiment 1:

[0055] Step S1: 5 mmol CsBr, 5 mmol PbBr2, 1 mmol BaBr2, and 2 g MCM-41 molecular sieve were ground and mixed uniformly. The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to heat at 450°C for 120 minutes, and then naturally cooled to room temperature to take out the sample powder.

[0056] Step S2: 300 mg of the calcined powder was dispersed in 30 ml of KF solution with a KF concentration of 3 mol / L. The mixed solution was placed in a 50 ml high-pressure reactor and the reactor was continuously heated at 180°C for 10 hours, and then naturally cooled to room temperature to obtain CsPbBr3 perovskite quantum dots with a fluorine-containing passivation layer.

[0057] Experimental analysis: Take the final product of the above preparation process and test its stability in a high temperature environment of 100°C and a strong blue light irradiation environment (350mW / cm2), see Table 1. After 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 84% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 76% of the original intensity. For comparison (see Comparative Example 1), the powder sample obtained only by high temperature calcination, under the same high temperature storage and blue light irradiation conditions for 100 hours, the luminescence intensity dropped to 20% and 33% of the initial intensity. The above results prove that the stability of perovskite quantum dots can be improved after hydrothermal treatment with KF solution.

[0058] like Figure 1 As shown, the perovskite nanocrystals are embedded in the lattice of the fluorine-containing passivation layer so that there is a passivation interface between the two. Combined with the data analysis in Table 1, it can be seen that the fluorine-containing passivation layer can passivate the surface defects of the perovskite nanocrystals and improve the stability.

[0059] Figure 2 1 is the XRD diagram of the perovskite quantum dots of Example 1 measured at various stages.

[0060] The MCM-41 molecular sieve selected in this embodiment contains sodium, potassium and aluminum ions, which are introduced during the doping, modification or synthesis stage to construct the characterization and identification phase NaK2AI F6.

[0061] Embodiment 2:

[0062] This example will demonstrate that other micro / mesoporous templates are also suitable for use in the present invention.

[0063] The present embodiment is different from the embodiment 1 in that mesoporous silicon oxide nanoparticles are used as the micro / mesoporous template.

[0064] Experimental analysis: The final product of the above preparation process was taken and its stability was tested in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 76% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 70% of the original intensity. As a comparison (see Comparative Example 2), the powder sample obtained by high temperature calcination alone, under the same high temperature storage and blue light irradiation conditions, after 100 hours, the luminous intensity dropped to 51% and 27% of the initial intensity.

[0065] Figure 3 3 is the XRD diagram of the perovskite quantum dots of Example 2 measured before and after hydrothermal treatment.

[0066] Embodiment 3:

[0067] Step S1: 5 mmol CsBr, 2.5 mmol PbBr2, 2.5 mmol Pb I2, 1 mmol BaBr2, and 2 g MCM-41 molecular sieve were ground and mixed uniformly. The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to heat at 450°C for 120 minutes, and then naturally cooled to room temperature to take out the sample powder.

[0068] Step S2: 300 mg of the calcined powder was dispersed in 30 ml of KF solution with a KF concentration of 3 mol / L. The mixed solution was placed in a 50 ml high pressure reactor and heated at 180 °C for 10 hours. The reactor was then cooled to room temperature to obtain CsPbBr with a fluorine-containing passivation layer. 1.5 I 1.5 Perovskite quantum dots.

[0069] Embodiment 4:

[0070] This example demonstrates that other inorganic fluoride solutions, such as NaF, CsF, and LiF, can also improve the stability of perovskite light emitters during the hydrothermal treatment stage.

[0071] The difference between this embodiment and embodiment 1 is that NaF, CsF and Li F are respectively used in the hydrothermal treatment stage, and the concentration and dosage of these fluoride solutions remain the same as those in embodiment 1.

[0072] Experimental analysis: Take the final product of the above preparation process and test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2). For the NaF hydrothermal treated sample, after 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 85% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 70% of the original intensity. For the CsF hydrothermal treated sample, after 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 83% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 77% of the original intensity. For the Li F hydrothermal treated sample, after 100 hours of high temperature storage, the luminescence intensity of the powder can maintain 89% of the original intensity; after 100 hours of continuous blue light irradiation, the luminescence intensity of the powder can maintain 71% of the original intensity. The above results prove that the stability of the perovskite luminophore can be improved after hydrothermal treatment with NaF, CsF, Li F and other solutions.

[0073] Comparative Example 1:

[0074] Grind and mix 5 mmol CsBr, 5 mmol PbBr2 and 2 g MCM-41 molecular sieve evenly.

[0075] The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to be heated at 450°C for 120 minutes, and then naturally cooled to room temperature to take out the sample powder.

[0076] Experimental analysis: The final product of the above preparation process was taken to test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 20% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 33% of the original intensity.

[0077] Comparative Example 2:

[0078] Grind and mix 5 mmol CsBr, 5 mmol PbBr2 and 2 g mesoporous silica nanoparticles evenly.

[0079] The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to be heated at 450°C for 120 minutes, and then naturally cooled to room temperature to take out the sample powder.

[0080] Experimental analysis: The final product of the above preparation process was taken to test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 51% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 27% of the original intensity.

[0081] Comparative Example 3:

[0082] 5mmol CsBr, 5mmol PbBr2, 1mmol BaBr2, and 2g MCM-41 molecular sieve were ground and mixed evenly. The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to heat at 450°C for 120 minutes, then naturally cooled to room temperature and the sample powder was taken out.

[0083] Take 300 mg of the calcined powder and disperse it in 30 ml of KF solution with a KF concentration of 3 mol / L. Soak it in water for 10 hours and then take out the sample powder.

[0084] Experimental analysis: The final product of the above preparation process was taken to test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 45% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 39% of the original intensity.

[0085] Comparative Example 4:

[0086] 5mmol CsBr, 5mmol PbBr2, 1mmol BaBr2, and 2g MCM-41 molecular sieve were ground and mixed evenly. The mixed powder was placed in a muffle furnace and heated from room temperature to 450°C, and continued to heat at 450°C for 120 minutes, then naturally cooled to room temperature and the sample powder was taken out.

[0087] Experimental analysis: The final product of the above preparation process was taken to test its stability in a high temperature environment of 100°C and in an environment of strong blue light irradiation (350mW / cm2), as shown in Table 1. After 100 hours of high temperature storage, the luminous intensity of the powder can maintain 26% of the original intensity; after 100 hours of continuous blue light irradiation, the luminous intensity of the powder can maintain 35% of the original intensity.

[0088] Table 1: Comparison of stability test results of samples from different embodiments (comparative examples)

[0089]

[0090]

[0091] The embodiments described above provide a detailed description of the preparation scheme of the present invention. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A perovskite quantum dot having a fluorine-containing passivation layer, characterized in that: It comprises a micro / mesoporous template with incompletely closed pores, wherein perovskite nanocrystals and a fluorine-containing passivation layer are grown in the pores of the micro / mesoporous template, and the fluorine-containing passivation layer is used to passivate the surface defects of the perovskite nanocrystals; The fluorine-containing passivation layer includes BaF2.

2. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 1, characterized in that: The fluorine-containing passivation layer is composed of BaF2 and other metal fluorides; The other metal fluorides are metal fluorides other than BaF2.

3. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 2, characterized in that: When the micro / mesoporous template is MCM-41, the fluorine-containing passivation layer is composed of BaF2 and NaK2AIF6.

4. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 1, characterized in that: The micro / mesoporous template is a microporous material and / or a mesoporous material; The microporous material is a microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride; The mesoporous material is mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.

5. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 1, characterized in that: The perovskite nanocrystal has a perovskite structure ABX3, wherein the molar ratio of A, B and X is 1:1:3, and A is Cs, B is Pb, Sn or Cu, and X is Cl, Br or I.

6. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 1, characterized in that: The perovskite nanocrystal has a perovskite structure ABX 1.5 X' 1.5 , wherein the molar ratio of A, B, X and X' is 1:1:1.5:1.5, and A is Cs, B is Pb, Sn or Cu, and X and X' are different and are independently Cl, Br or I.

7. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 1, characterized in that: The melting point of the fluorine-containing passivation layer is higher than the melting point of the perovskite nanocrystals.

8. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 7, characterized in that: A passivation interface is provided between the fluorine-containing passivation layer and the perovskite nanocrystal.

9. The perovskite quantum dot having a fluorine-containing passivation layer according to claim 8, characterized in that: Perovskite nanocrystals are embedded in the lattice of the fluorine-containing passivation layer; or, part of the perovskite nanocrystals are covered by the fluorine-containing passivation layer.

10. A method for constructing a fluorine-containing passivation layer of a perovskite quantum dot, characterized in that: It comprises a micro / mesoporous template with incompletely closed pores, wherein perovskite nanocrystals containing barium are grown in the pores of the micro / mesoporous template, and a lead hydroxide coating layer is formed on the surface of the perovskite nanocrystals after being soaked in water; Also included are F ions enriched in the pores of the micro / mesoporous template, and the lead hydroxide coating layer blocks the F ions and the barium-containing perovskite nanocrystals; Under the hydrothermal reaction, the lead hydroxide coating disappears and a BaF2 passivation layer is formed on the surface of the perovskite nanocrystals.

11. The method for constructing a fluorine-containing passivation layer of a perovskite quantum dot according to claim 10, characterized in that: When the fluorine-containing passivation layer is composed of BaF2 and other metal fluorides, the other metal fluorides can be used as characterizing identification phases for constructing the fluorine-containing passivation layer of perovskite quantum dots through a hydrothermal reaction.

Citation Information

Patent Citations

  • Method for growing halide perovskite nanocrystals through in-situ chemical vapor deposition

    CN116752116A

  • Perovskite nanocrystalline fluorescent material and preparation method and application thereof

    CN118165723A

  • Method for improving stability of perovskite nanocrystals and application

    CN119552648A

Cited By

  • Preparation method of perovskite quantum dots with in-situ self-coated double shell layers

    CN120424654A

  • Method for obtaining small-size perovskite illuminant through post-treatment

    CN120590946A